Business Model Analysis of Halal Transportation Provider Company - Anggara, Fajar Surya Ari; Wijaya, Wisnu (Universitas Semarang, 2021)
Halal products have become important needs for the Muslims. Increasing demand for halal products increased to encourage the importance of halal logistics. Halal logistics system must guarantee that the products remain secured in the process of logistic and transport activities. There is still many homework to be done to realize halal transportation and logistics in Indonesia.TRAC Sharia as a transportation services provides a solution that is established with sharia principles such as musyarakah, mutanaqisah, and ijarah through its business process model. Novelty of this study is on the mapping of value proposition, business model, and business process integrated with Sharia principles. According to the results of this research that TRAC Sharia provides the best Ijarah services for companies that are concerned about sharia-based products or services. Agreement of Ijarah on TRAC Sharia is free from the elements of Riba, Maysir, and Gharar. In addition, all vehicles TRAC Sharia obtained halal through murabahah mechanisms and protected by insurance based on Sharia principles (Ta'awun). The advantage of TRAC Sharia is the openness and fairness in the management of the vehicle and can be developed into a mudharabah with the concept of profit sharing.